The genus Helicotylenchus steiner, 1945 in West Malaysia. - Sauer, M. R.; Winoto, R. (Brill Academic Publishers, 1975)
Species of Helicotylenchus are common in the soils of West Malaysia, both cultivated and uncultivated. The most widely distributed species are H. dihystera (Cobb) and H. multicinctus (Cobb). H. pseudorobustus (Steiner), H. abunaamai Siddiqi, and H. crenacauda Sher, have also been identified from cultivated soils. H. erythrinae (Zimmermann) and two new species H. pasohi and H. paracanalis, have been found in uncultivated jungle soil. H. pasohi is a bisexual species close to H. exallus Sher, with more posteriorly placed vulva, indented tail, and phasmids at anal level. H. paracanalis is close to H. canalis Sher with prominent lateral canals, but is bisexual.